USE OF SEMINAR WITH A MYSTIQUE IN THE POST-GRADUATE EDUCATION: EXPERIENCE REPORT (Fiep Bulletin - online, 2013)
This article is an experience report about the use of seminary as a mystic in post-graduation education. The goal is to present the experience in using the seminary as a methodology of post-graduation teaching in nursing. The relevance of this study comes from the knowledge of the importance of using the seminary as a teaching methodology to post-graduation, putting the mystic as a possibility to live inspiration and feelings, capable of reveling opinions, ideas and relate the world's context with questions related to nowadays society, current from the scientific development.
Keywords: Teaching; seminary; mystic